Answer:
x=12
Explanation:
Simplifying 5x + -9 = 3x + 15 Reorder the terms: -9 + 5x = 3x + 15 Reorder the terms: -9 + 5x = 15 + 3x Solving -9 + 5x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 5x + -3x = 15 + 3x + -3x Combine like terms: 5x + -3x = 2x -9 + 2x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 2x = 15 + 0 -9 + 2x = 15 Add '9' to each side of the equation. -9 + 9 + 2x = 15 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 15 + 9 2x = 15 + 9 Combine like terms: 15 + 9 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12